Simplified down sampling factor based modified SVPWM technique for cascaded inverter fed induction motor drive - Ravi Kumar Bhukya; P. Satish Kumar (Institute of Advanced Engineering and Science, 2020)
This paper presents a rivew, investigation and performance analysis of novel down samples factor based modified space vector PWM is called clamping SVPWM technique for cascaded Multilevel Invereter fed to Induction motor drive. In this paper the reference sine wave generated as in case of conventional off set injected SVPWM technique is modified by down sampling factor the reference wave by order of 10. The performance analyses of this modulation strategies are analyzed by apply for five level, seven level, nine level and eleven level inverter. The performance analysis of cascaded inverter interms of line voltage, stator current, speed, torque and total harmonic distortion. The results are depicting that PD PWM is more effective among the four proposed PWM technique. It is observed that the CSV Pulse width modulation ensures excellent, close to optimized pulse distribution results compared to SPWM technique and also 11-level inverter beter performance in case of low THD and better foundemental output voltages comapared to 5, 7, 9-level inverter. The proposed technique has been simulated using MATLAB/SIMULINK software. This proposed technique can be applied to N-level multilevel Inverter also.